Pengembangan Media Audio Visual Cerita Rakyat dalam Pendidikan Karakter di SD Negeri Rejosari 03 - Diah Utami; Prasena Arisyanto; Ervina Eka Subekti (STKIP Andi Matappa Pangkep, 2023)
The application of the lecture method and personal approach to students in character education at SD Negeri Rejosari 03 has been going well, but in this case there are still some problems related to character education, it is necessary to develop learning media, one of which is by using the wrong learning media. the only audio-visual media of folklore. The development of folklore audio-visual learning media that contains character education values aims to support student character development. The method used in research is Research and Development. This research aims to develop an existing product or produce a product. The results obtained from media experts I 100%, media experts II 100%, and media experts III 91.11%. The results obtained by material experts I 100% and material experts II 100% and material experts III 88.88% with the criteria